Analysis of Pedagogical Practices with Deaf-Blind Students in Five Regions of Chile at Both Integrated1 and Special Need Schools - Donoso Araya, Oriana Elizabeth (2021)
This article encompasses one component of a study on communication skills among deaf-blind students and didactic interactions with their teachers. The objective of this field study was to examine the diferent proficiency levels of the teaching faculty with regards to this disability and based on didactic interactions with their students. The selected teachers either taught at special needs schools or integrated schools participating in the inclusion program. The study was based on a qualitative case study with a sample of twelve deaf-blind individuals from five regions of Chile. The conclusion provides specific teaching recommendations about deaf-blind communication and reveals the existence of knowledge gaps among teachers with regards to communicating with their deaf-blind students. Suggestions were made to improve communication and didactic interactions to overcome existing methodological teaching hurdles when teaching this population group.